Efficacy and safety of alternative-level laminoplasty vs. all-level laminoplasty: a systematic review and meta-analysis - Zheng, Bin; Ma, Ke; Zhu, Zhenqi; Liu, Haiying (Frontiers in Surgery, 2025)
BackgroundThis study systematically reviews the literature and performs a meta-analysis to evaluate and compare the intra-operative outcomes, clinical efficacy, safety, and cost of alternative-level and all-level laminoplasty.MethodsA systematic review is conducted according to the PRISMA guidelines. Searches are performed in PubMed, Cochrane Library, OVID, and Embase databases from inception to August 2024, using search terms “laminoplasty” AND “all OR skip OR alternative.” Data extraction and risk-of-bias assessment are conducted independently by two researchers using the Newcastle-Ottawa Scale. Statistical analysis is performed with RevMan 5.4.ResultsFour retrospective Chinese studies (337 patients: 176 alternative-level, 161 all-level) meet the criteria. Meta-analysis shows no significant difference in intra-operative outcomes: operative time (P = 0.23) and blood loss (P = 0.11). Clinical efficacy, measured by Japanese Orthopaedic Association(JOA) Score (P = 0.08), JOA recovery(P = 0.08), and Visual Analog Scale (P = 0.26), also shows no significant difference. Similarly, safety outcomes, including complications(P = 0.64), C5 palsy(P = 1.00), and axial symptoms(P = 0.57), are comparable between the two fixation methods. Cervical sagittal parameters are also equivalent: Cervical Curvature Index (P = 0.18) and overall range of motion (P = 0.29). However, alternative-level laminoplasty demonstrates lower cost (P < 0.00001) and is inferior in cervical canal outcomes, including anterior–posterior diameter (P = 0.01), Pavlov ratio(P = 0.007) and open angle (P < 0.00001).ConclusionAlternative-level laminoplasty matches all-level fixation in operative efficiency, neurological recovery, and complication rates while substantially reducing implant costs. Its slightly lesser canal expansion does not translate into inferior clinical outcomes. Evidence strength is limited by the small number of single-center retrospective studies from one country. Multi-center randomized trials in other countries are needed to confirm generalizability.